Studi Kritis Bahan Ajar Mata Pelajaran Tafhim Al-Qur’an dalam Materi Amanah Kelas II Smp-T Darul ‘Amal - Emat Muslihat; Siti Qomariyah; Tedi Tedi; Hendi Supandi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The instillation of trustworthiness (amanah) is an essential element in the character development of students, particularly within the framework of Islamic education. As a core moral value emphasized in both the Al-Quran and Hadith, amanah serves as a foundation for shaping students' integrity, responsibility, and reliability. Despite its significance, the teaching materials designed to instill this value have not been critically assessed, especially in terms of their content relevance and pedagogical effectiveness. This study aims to conduct an in-depth analysis of the Tafhim Al-Quran teaching materials used for Grade II students at SMP-T Darul 'Amal, focusing on the topic of amanah. Utilizing a qualitative approach with a descriptive method, data were gathered through the collection of documents, lesson plan (RPP) reviews, and interviews with subject teachers. The findings reveal that the teaching materials do cover the three learning domains—cognitive, affective, and psychomotor—but tend to disproportionately emphasize the cognitive domain. While the materials include references to Al-Quran verses and Hadith concerning trustworthiness and the fulfillment of promises, they often lack practical, real-world examples that are relatable to the everyday experiences of adolescents. Moreover, the current instructional approach remains conventional and teacher-centered, offering limited opportunities for students to engage in reflective and participatory learning activities. In light of these findings, the study recommends the development of more contextualized and student-centered teaching materials. These materials should incorporate active learning strategies, such as group discussions, case studies, and experiential learning activities, to more effectively foster the internalization of amanah as a lived value. Enhancing the relevance and interactivity of character education in this way can significantly improve its impact on students' moral development.